Neurophysiological and Neuroradiological Changes in Children With Chronic Kidney Disease - Abd El Naby, Sameh A.; Bahbah, Wael A.; Kasemy, Zeinab A.; Mahmoud, Asmaa A. (Frontiers in Pediatrics, 2020)
Background: Patients with chronic kidney disease (CKD) on maintenance hemodialysis frequently present with neurological complications. These complications include peripheral neuropathy, encephalopathy, and stroke. Objectives: To detect the prevalence of neurological manifestations and complications in children with CKD through neurophysiological and neuro-radiological findings. Methods: The study included 50 patients with CKD admitted to a pediatric nephrology unit. Their history and complete physical and neurological examination findings had been recorded. All patients underwent nerve conduction, electromyography, electroencephalography, and magnetic resonance imaging of the brain. Results: Fifty children of both sexes (23 males and 27 females) with a mean age of (12.08 ± 3.46 year) were studied. Eleven (22%) patients with CKD developed polyneuropathy, mostly of an axonal polyneuropathy pattern, while 39 (78%) of them showed normal electrophysiological studies. No myopathy was detected. Abnormal electroencephalography findings were detected in 18% of patients, mostly generalized and focal (temporal, occipital, and frontal) epileptogenic activity. Abnormal MRI brain findings were detected in 16% of patients, mostly of encephalomalacia. Conclusion: Uremic neuropathy was highly prevalent in children with CKD on maintenance hemodialysis. They developed polyneuropathy, mostly of an axonal polyneuropathy pattern. EEG is a useful method for early recognition of subclinical uremic encephalopathy and/or epileptogenic activity. Early demonstration and management of uremic neurological conditions may decrease the physical disability of CKD patients.